PEMANFAAT PELEPAH KELAPA SAWIT SEBAGAI USAHA KREATIF DALAM MENUNJANG PEREKONOMIAN MASYARAKAT DESA NAKAU - BENGKULU TENGAH - Melly Susanti; Ermi Wijaya (LPPM - STIE SAKTI ALAM KERINCI, 2019)
Abstrack The research was carried out with the aim of providing direct insight to the community regarding the utilization of oil palm waste as a productive product with selling value. The research that will be carried out is descriptive research that describes how the process and results of the utilization of oil palm waste. The population in this study was the people in Nakau Village, Central Bengkulu Regency. The research subjects were the target of nakau villagers who owned oil palm plantations. The research was carried out by simulating the production of products and continued design independently. The method of conducting the study consisted of: (1) field survey, (3) coordination to the village, (4) socialization, (5) simulation, and (6) dissemination of public response questionnaires. The data collection tool consists of interview sheets and public response questionnaire sheets. Through this activity, the community is expected to be able to utilize oil palm fronds and farmers have solutions for oil palm fronds.